Observance of the national interests of the Republic of Kazakhstan in the preparation, adoption and execution of regulatory legal acts (Journal of actual problems of jurisprudence, 2022)
The article analyzes the current legislation of the Republic of Kazakhstan for the development, adoption and execution of legislative and other regulatory legal acts in the field of national security. Scientific expertise is considered as the main tool in assessing the quality and effectiveness of the rule-making process, while the author emphasizes that the types of scientific expertise carried out in the Republic of Kazakhstan (legal, economic, anti-corruption, environmental) are able to ensure compliance with national security requirements only partially.The most promising way to ensure the safety of the law-making process in the article is to conduct a scientific examination for compliance with national interests as an independent type of examination. Developing positions on the introduction of an independent type of scientific expertise for compliance with national interests, it should be noted that it should not be limited only to the stage of preparation of the draft law. Scientific expertise on the observance of national interests should be applied to the existing regulatory legal acts, which, together with the Institute of Legal Monitoring, will be aimed at ensuring the quality and effectiveness of legal regulation of public relations in the Republic of Kazakhstan.Within the framework of the scientific project No. AR14872048: Development of measures to ensurethe national security of the Republic of Kazakhstan in the legislative sphere.Keywords: national security, legislation, scientific expertise, regulatory legal act, national interests, international treaties.